Model Latihan Passing Futsal Berbasis Small Sided Games Untuk Siswa Sekolah Menengah Atas - Praniata, Agus Rizqi; Kridasuwarso, Bambang; Puspitorini, Wahyuningtyas (Journal Sport Area, 2019)
This research aimed to determine the effectiveness of futsal passing training models based small-sided games at the high school level. This type of research was research and development design with the type of one group pretest-posttest design. The sample used in this study was futsal athletes in high school students in the city of Bandung. Data collection techniques in this research were collected by test and observation. The results showed that the mean score of experimental group was 7.3333 and control group was 8.4000. Then, the results of the experimental group and the control group or the mean difference was -1.06667, t-count was -4,547, df was 58, with p-value as 0,000 which was smaller than 0.05. So, it can be concluded that there was significant effect of using small-side game of futsal passing trainings.